Investigation of tensile strength performance of green concrete incorporating steel slag - Opeyemi K. Olayanju (Hybrid Advances, 2024)
This study examined the compressive and tensile strength performance of steel slag-containing concrete composites in a sulphate environment. Steel slag sourced locally was mechanically crushed and sieved into aggregates ranging in size from 20 to 1 mm. The control concrete of grade 20 and other five (5) batches of concrete with 10 to 50% steel slag at a step of 10% as replacement for natural coarse aggregate were produced. The physical properties of the aggregate specimens (steel slag and granite) were evaluated in the laboratory, as well as the concrete workability and the 7- and 28-day compressive and tensile strengths after exposure to 50 g/l of magnesium and sodium for 7 and 28 days. According to the results, the concrete workability decreased as the steel slag content increases. The 20 N/mm2 desire strength with rise in compressive and split tensile strengths as the steel slag contents increased from 0 to 50% after curing in water for 28 days. The concrete compressive and tensile strengths improved with steel slag content ranging from 0 to 40% but decreased with increase in steel slag content from 30 to 50% after exposure to Na2SO4 for 28 days. For the concrete exposed to MgSO4, the compressive and split tensile strengths increased when the steel slag content increased from 0 to 40% before it decreased with further increase in steel slag from 40 to 50% after 28 days. The experimental findings revealed that up to 40% steel slag is sufficient as replacement for natural coarse aggregate in concrete work exposed to aggressive sulphate climate. Thus, for improved compressive and tensile performance, the optimum of 40% steel slag is suggested as replacement for natural coarse aggregate substitution for healthier sulphate attack resistance.